Influencia del estrés laboral en el desempeño de los docentes del centro educativo particular La Inmaculada de Trujillo - Perú 2015 - Chávez Quiñones, Rocío del Pilar (2016)
The present investigation had as aim determine the influence of the job stress in the performance of the teachers of the Educational Particular Center the Immaculate Conception of Trujillo 2015. This one had as purpose to identify the principal factors of risk of the stress and its influence in the performance of them, for which realized a not experimental, descriptive study and of transverse court. There was applied as instrument of measurement to the sample a questionnaire of job stress (CEL), using Likert's scale (on stress in teachers), validated by two professionals of the area of psychology. In the statistical analysis, Kolgomorov Smirnov's test was used to determine the normality of the information, and the test of association Chi Cuadrado, and Tau-b de Kendall or Tau-c de Kendall to determine the Influence of the job stress in the performance of the teachers, using the statistical package SPSS version 22 as support for the processing of information. The results showed that the instrument possesses internal consistency, reliability and validity of constructo adapted that allowed to identify the factors of the job stress as: The load of work and the relation with the pupils with 72.5 % respectively, the relation with the family parents with 60.8 %, the conflict and ambiguity of functions with 51 %, the relation with the colleagues with 56.9 % and the institutional climate with 80.4 %. Likewise there were identified the factors of the educational performance between which we have: the safety and permanency with 54.9 %, the establishment of aims with 70.6 %, the condition of work with 86.3 %, promotion and development of the teacher with 52.9 %, recognition as important person 47.1 %. One concluded that the job stress influences significantly the performance of the teachers, in an average level with 88.6%. The main recommendation to the one that came near is that the executives of the educational center must promote actions of prevention and managing of the job stress that allow to improve the working conditions and it could achieve an appropriate educational performance, since according to the experts the positive working conditions can increase the performance of the teacher.